HS3ST2 modulates breast cancer cell invasiveness via MAP kinase‐ and Tcf4 (Tcf7l2)‐dependent regulation of protease and cadherin expression. Issue 11 (30th April 2014) - Vijaya Kumar, Archana; Salem Gassar, Ezeddin; Spillmann, Dorothe; Stock, Christian; Sen, Yin‐Ping; Zhang, Ting; Van Kuppevelt, Toin H.; Hülsewig, Carolin; Koszlowski, Eliene O.; Pavao, Mauro S.G.; Ibrahim, Sherif A.; Poeter, Michaela; et al.
Abstract : Heparan sulfate 3‐ O ‐sulfotransferase 2 (HS3ST2), an enzyme mediating 3‐ O ‐sulfation of heparan sulfate (HS), is silenced by hypermethylation in breast cancer. As HS has an important co‐receptor function for numerous signal transduction pathways, the phenotypical changes due to HS3ST2 reexpression were investigated in vitro using high and low invasive breast cancer cell lines. Compared to controls, highly invasive HS3ST2 ‐expressing MDA‐MB‐231 cells showed enhanced Matrigel invasiveness, transendothelial migration and motility. Affymetrix screening and confirmatory real‐time PCR and Western blotting analysis revealed increased expression of several matrix metalloproteinases, cadherin‐11, E‐cadherin and CEACAM‐1, while protease inhibitor and annexin A10 expression were decreased. Low invasive HS3ST2 ‐expressing MCF‐7 cells became even less invasive, with no change in gelatinolytic MMP activity. HS3ST2 expression increased HS‐dependent basal and FGF2‐specific signaling through the constitutively active p44/42 MAPK pathway in MDA‐MB‐231 cells. Increased MAPK activation was accompanied by upregulation of ß‐catenin in MDA‐MB‐231, and of the transcription factor Tcf4 in both cell lines. Dysregulation of Tcf4‐regulated ion transporters and increased cytosolic acidification were observed in HS3ST2 ‐expressing MDA‐MB‐231 cells, which is a possible underlying cause of increased chemosensitivity towards doxorubicine and paclitaxel in these cells. This study provides the first in vitro evidence of the involvement of HS3ST2 in breast cancer cell invasion and chemosensitivity. Abstract : What's New? Heparan sulfate is present in all cell types and tissues and is involved in the modulation of cell adhesion, proliferation, and motility. While HS3ST2— an enzyme mediating 3‐ O ‐sulfation of heparan sulfate—is known to be epigenetically silenced in breast cancer, its mechanistic role has yet to be characterized. This study reveals a novel role of HS3ST2 in modulating breast cancer cell invasiveness and chemoresistance via MAP kinase‐ and Tcf7l2/Tcf4‐dependent regulation of protease and cadherin expression. The findings demonstrate the importance of specific sulfation patterns in heparan sulfate and pave the way for new heparinoid‐based therapeutic approaches.